2021
DOI: 10.3390/molecules26144369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiproliferative Palladium(II) Complexes of Synthetic Bisdemethoxycurcumin towards In Vitro Cytotoxicity and Molecular Docking on DNA Sequence

Abstract: Metallodrugs form a large family of therapeutic agents against cancer, among which is cisplatin, a paradigmatic member. Therapeutic resistance and undesired side effects to Pt(II) related drugs, prompts research on different metal–ligand combinations with potentially enhanced biological activity. We present the synthesis and biological tests of novel palladium(II) complexes containing bisdemethoxycurcumin (BDMC) 1 and 2. Complexes were fully characterized and their structures were determined by X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…On the other hand, since all currently available antibiotics will inevitably develop resistance, the development of novel antibiotic replacement therapies is urgently required. Naturally sourced antibacterial agents are considered to have extremely low drug resistance due to their rich sources and diverse and complex structures [26]. Based on this,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, since all currently available antibiotics will inevitably develop resistance, the development of novel antibiotic replacement therapies is urgently required. Naturally sourced antibacterial agents are considered to have extremely low drug resistance due to their rich sources and diverse and complex structures [26]. Based on this,…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since all currently available antibiotics will inevitably develop resistance, the development of novel antibiotic replacement therapies is urgently required. Naturally sourced antibacterial agents are considered to have extremely low drug resistance due to their rich sources and diverse and complex structures [26]. Based on this, we additionally conducted a preliminary trial of the BDMC resistance test, and the results showed that BDMC had no apparent resistance after 10 consecutive passages (45 days), and the resistance effect was better than that of the traditional antibiotic linezolid in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Palladium (Pd) is a highly valuable metal that possesses catalytic, structural, and electroanalytical characteristics. 104 Palladium (PdNMs) are being used as self‐therapeutics and have been shown to exhibit antibacterial and cytotoxic properties. 105 When compared to other bacterial strains, Escherichia coli , PdNPs demonstrated a high level of growth inhibition against Staphylococcus aureus , indicating that they are useful against antibacterial agents, especially for gram‐positive bacteria.…”
Section: Applications Of Metal‐based Nms In Different Types Of Cancermentioning
confidence: 99%
“…Palladium (Pd) is a highly valuable metal that possesses catalytic, structural, and electroanalytical characteristics 104 . Palladium (PdNMs) are being used as self‐therapeutics and have been shown to exhibit antibacterial and cytotoxic properties 105 .…”
Section: Applications Of Metal‐based Nms In Different Types Of Cancermentioning
confidence: 99%
“…BDMC inhibits cell proliferation, invasion and migration, metastasis, and tumor growth and induces apoptosis in tumor cells, and generates ROS levels in breast cancer, lung cancer, gastric cancer, and ovarian cancer [ 15 , 16 ]. It may act also as a potential novel antimetastatic agent for the treatment of human cervical cancer by suppressing migration and invasion of HeLa cells via inhibition of NF- κ B, MMP-2, and -9 pathways [ 17 , 18 ]. BDMC can significantly alleviate in vivo nephrotoxicity caused by cisplatin through anti-oxidant and anti-inflammatory effects and has a synergistic anti-cancer effect with cisplatin [ 19 ].…”
Section: Introductionmentioning
confidence: 99%